The perfection and self-sufficiency of the Qurʾān in the law of inheritance (part one) - Tahir, Ibrahim Nuhu (International Islamic University Malaysia, 2015)
This paper addresses the law of inheritance detailed in the Book of Allah, the Qur’an. It is about a system that Allah took complete responsibility of its explanation in detail. This is different from the norm, whereby Allah gives the general ruling and its details or explanation will be given by the Prophet (sal-Allahu 'alayhi wa sallam). This attitude itself indicates the great position held by this knowledge. Islam values family unity and integration. Family disputes, disintegration and severing of ties can occur if shares of the estate are not placed in their correct position. Allah The Almighty has taken the said responsibility of explaining it in detail to the Ummah to prevent dysfunctional and broken families. The researcher relies solely on the Qur’an and some sources which are also relying on the Qur’an. The work aims to expose the beauty of the concise information about inheritance mentioned in the Qur’an. The method of the Qur’an is so comprehensive covering all the heirs of the deceased (with the exception of the grandmother) even though the ayat that tackled the issue are not more than four. This research is comprised of two separate articles: PART ONE which discusses the first type of inheritance (inheritance with Far’d) and PART TWO where the second type (inheritance with Ta'sib) is discussed. In this article each set of conditions that qualify an heir to inherit a fixed share is accompanied by a table that illustrates their application.